Differences in motor abilities of various types of European young elite female basketball players - Erculj, F.; Blas, M.; Coh, M.; Bracici, M. (Kinesiology, 2009)
The study is mainly aimed at determining and analysing motor abilities of European top-quality young female basketball players. Our primary interest was the development level of motor abilities of various types of players and probable differences between them. The sample of subjects consisted of 65 female basketball players from 27 European countries aged 14.49±.62 who were divided into three groups according to their playing positions (guards, forwards, centres). Using eight motor tests, we mainly investigated the players` motor abilities as follows: power of sprinting type, agility, power of throwing type and power of jumping type. Basic descriptive statistics was calculated for all the groups and the differences between them were established using ANOVA, MANOVA and MANCOVA with body height and mass as covariates. The study results show that the differences between individual player types can also be confirmed in a sample of European top-quality young female basketball players. They were distinctly differentiated in body height and mass, whereas ANOVA and MANOVA also confirmed the differences in their motor abilities. The structure of motor abilities of individual player types changes considerably if the influence of body height and mass is eliminated. The differences between them decrease and are only preserved in the technically most demanding movements performed with the ball. The differences are not only a consequence of the differences in body height but also of the different playing roles of individual types of players as well as the required technical knowledge.